Innovations in enterprise information systems management and engineering : 5th International Conference, ERP Future 2016 - Research, Hagenberg, Austria, November 14, 2016, Revised Papers /: 5th International Conference, ERP Future 2016 - Research, Hagenberg, Austria, November 14, 2016, Revised Papers. (2017) - Unknown
No abstract available